Occupational complexity of paid work and housework, and its impact on the cognitive performance in community dwelling older adults, preliminary results - Feldberg, Carolina (2023)
Work and activity could be an important source of cognitive enrichment. Activities that are more challenging concerning the cognitive functions that are put into practice are associated with lower risk of cognitive decline in old age. Objective: The present study aimed to assess the impact of occupational complexity and household tasks in three cognitive domains (verbal episodic memory, language, and executive functions) in older adults residing within the community. Methods: A trail analysis was executed, using the structural equations procedure in 120 participants assessed with main lifetime occupational activity and household tasks questionnaire, as well as a neuropsychological assessment battery for memory, language, and executive functions. Results: The regression weights analysis indicated that complexity in household chores showed moderate effects on executive functions (β=0.19; p=0.027) and that occupational complexity of paid work showed effects on memory (β=0.26; p=0.008), language (β=0.38; p<0.001), and executive functions (β=0.55; p<0.001). Conclusion: Paid work promotes cognitive reserve, contrary to household activities which seem to have a moderate impact on cognition. Differences in activity complexity not only impact people´s economic and social status and possibilities but can also determine different courses of aging and cognitive risk.